Successful Obstetrical Management of Dystocia Due to Schistosomus Reflexus Foetus in a Kankrej Cow – A Case Report - S. Rangasamy; S. Alagar; S. Sathishkumar; J. Umamageswari; R. Sureshkumar; D. Reena; K. Ravikumar (The Indian Veterinary Journal, 2024)
Schistosomus reflexus (SR) is a rare and fatal congenital malformation found in bovines, stemming from autosomal recessivedisorders. This anomaly primarily manifests in cattle, affecting the foetus’s trunk and often leading to dystocia during birth (Roberts, 1971). A review of existing literature shows limited documentation regarding the occurrence of schistosomus reflexus in Kankrej cows. Therefore, this communication presents a case study detailing dystocia resulting from schistosomus reflexus in a pluriparous Kankrej cow.